2015
DOI: 10.1016/j.celrep.2015.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Derived Tick Repellents Activate the Honey Bee Ectoparasitic Mite TRPA1

Abstract: We have identified and characterized the TRPA1 channel of Varroa destructor (VdTRPA1), a major ectoparasitic mite of honey bee. One of the two VdTRPA1 isoforms, VdTRPA1L, was activated by a variety of plant-derived compounds, including electrophilic compounds, suggesting that chemical activation profiles are mostly shared between arthropod TRPA1 channels. Nevertheless, carvacrol and α-terpineol activated VdTRPA1L but not a honey bee noxious-stimuli-sensitive TRPA, AmHsTRPA, and Drosophila melanogaster TRPA1. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 50 publications
2
38
0
Order By: Relevance
“…41,42) In fact, plant-derived repellents carvacrol and alpha-terpineol that activate the varroa mite TRPA1L channel but not the honey bee HsTRPA channel repressed mite entry into brood cells in hives, showing some potential for the use of TRPA1-activating compounds in apiculture. 43) TRPA1 operating downstream of -Gq/phopshoplipase C signaling cascade is also required in Drosophila for the avoidance of the repellent citronellal, whereas the Anopheles gambiae TRPA1 is directly activated by citronellal. 44) The roles of Pain and Pyx in detecting noxious heat have already been mentioned above.…”
Section: Trpamentioning
confidence: 99%
“…41,42) In fact, plant-derived repellents carvacrol and alpha-terpineol that activate the varroa mite TRPA1L channel but not the honey bee HsTRPA channel repressed mite entry into brood cells in hives, showing some potential for the use of TRPA1-activating compounds in apiculture. 43) TRPA1 operating downstream of -Gq/phopshoplipase C signaling cascade is also required in Drosophila for the avoidance of the repellent citronellal, whereas the Anopheles gambiae TRPA1 is directly activated by citronellal. 44) The roles of Pain and Pyx in detecting noxious heat have already been mentioned above.…”
Section: Trpamentioning
confidence: 99%
“…Two transcripts were assigned to the TRP group; both possess a 'TRP' annotation in the BLAST hit and the two functionally important domains: the transient receptor ion channel domain (TRP_2, IPR013555) as well as the protein-binding site of the ankyrin repeat (IPR002110) (Peng, Kashio, et al, 2015). A local BLASTn search, using the reported Varroa VdTRPA1-L as query (accession ID: AB930121), found high similarity to one of the two TRPs in the current study (TRINITY_DN30598_c0_g1_i2, e-value = 8.81E-10).…”
Section: Annotation Of Chemosensory-related Transcripts and Proteinsmentioning
confidence: 99%
“…Interestingly, all upregulated transcripts are clustered together in the phylogenetic analysis, along with other arachnid sequences, whereas transcripts not exhibiting differential expression clustered closer to D. melanogaster ENaCs. In particular, the L isoform of the receptor is activated by electrophilic compounds as well as various plant-derived tick repellents, specifically α-terpineol, which also repelled Varroa in laboratory and hive experiments (Peng, Kashio, et al, 2015). However, their expression profiles in chemosensory organs and their functions have not been evaluated.…”
Section: Potential Specialization Of Enacs and Trps As Chemoreceptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some reports indicate that α-terpineol possesses inhibitory effects on nerves. In a recent study, Peng et al [18] revealed that α-terpineol activates the TRPA1 channels of Varroa destructor, a major ectoparasitic mite of the honeybee. Such findings raise the possibility that α-terpineol is a candidate to induce inhibition of nerve conduction by acting on TRP proteins.…”
mentioning
confidence: 99%